2005
DOI: 10.1128/jvi.79.21.13685-13693.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Norovirus Protease Structure Provides Insights into Active and Substrate Binding Site Integrity

Abstract: Norovirus 3C-like proteases are crucial to proteolytic processing of norovirus polyproteins. We determined the crystal structure of the 3C-like protease from Chiba virus, a norovirus, at 2.8-Å resolution. An active site including Cys139 and His30 is present, as is a hydrogen bond network that stabilizes the active site conformation. In the oxyanion hole backbone, a structural difference was observed probably upon substrate binding. A peptide substrate/enzyme model shows that several interactions between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
131
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(143 citation statements)
references
References 51 publications
12
131
0
Order By: Relevance
“…This limitation in the cultivation of calicivirus has hampered studies on the replication strategies of these important human and animal pathogens. An alternative approach to cell-based studies has relied on structural and functional characterization in vitro of the viral enzymes putatively implicated in replication, such as the viral polymerase (4,17,21,43,44,50,51,59,60,62), the viral protease (5,40,45,(54)(55)(56)65), or the viral NTPase (36,48). Furthermore, reverse genetic systems for Norwalk virus (norovirus) (3,28) and porcine enteric calcivirus (sapovirus) have been developed (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This limitation in the cultivation of calicivirus has hampered studies on the replication strategies of these important human and animal pathogens. An alternative approach to cell-based studies has relied on structural and functional characterization in vitro of the viral enzymes putatively implicated in replication, such as the viral polymerase (4,17,21,43,44,50,51,59,60,62), the viral protease (5,40,45,(54)(55)(56)65), or the viral NTPase (36,48). Furthermore, reverse genetic systems for Norwalk virus (norovirus) (3,28) and porcine enteric calcivirus (sapovirus) have been developed (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the active-site residues of the 3C-like proteases of the NoV Chiba virus strain and the RHDV FRG strain have been identified by site-directed mutagenesis (5,14,36,46). Recently, the X-ray crystal structures of the two 3C-like proteases of NoV (Chiba and Norwalk strains) were determined (27,46). In contrast, although site-directed mutagenesis of the 3C-like proteases of the SaV Mc10 and FCV Urbana strains showed that C in the GDCG motif is crucial for the proteolytic processing activity (28)(29)(30), the remaining amino acids that are important for the activity have not been identified.…”
mentioning
confidence: 99%
“…The mature proteins include an RNA-dependent RNA polymerase (RdRp) (NS7 pol ), an ATPase (NS3), and proteins that disrupt cellular trafficking (NS1-2 and NS4) (18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%